Community Organization and Mobilization Experiences of Social Work Students - Cepeda, Merlinda C. (Silliman Journal, 2022)
This article describes the community organizing and mobilizing efforts of students with the community residents whoparticipated in the service-learning program. Results of these efforts showed that community work was not only an academic requirement but an opportunity for students to enrich their values of service. Working with various sectors in the community which included women, men, and the youth contributed to their feelings of satisfaction and personality enhancement. Following a set of activities that included community entry and integration, informal community study, core group formation, problem assessment, and planning of community activities, they implemented various activities with the community residents together with students from other disciplines. As their journals reveal, the students learned many significant lessons from these collective endeavors with the community which enhanced their values to serve and work with the common people.